Detection of avian metapneumovirus field infection via reverse transcriptase polymerase chain reaction (RT-PCR) and ELISA in two layer farms in Johore - Lim, A. A. S.; Abu, Jalila; Choo, Pow Yoon; Jaganathan, Seetha; Goh, Yong Meng (Veterinary Association Malaysia, 2009)
Avian metapneumovirus (AMPV) infection which is known as 'swollen head syndrome' has been shown to be prevalent in poultry farms in Malaysia. Two layer farms in Johor denoted as Farm A and Farm B, with previous history of AMPV disease outbreak, were the subjects used for the AMPV field investigation in this study. Thirty chicks from respective treatment groups were monitored at day old, two, four and six weeks of age for AMPV antibody and antigen detection. RT-PCR and ELISA serology indicate that at 2 weeks of age. AMPV field infection had occured in Farm A. In Farm B, AMPV field infection or lateral spread of vaccine was observed as early as 2 weeks. AMPV seroconversion was generally observed at four weeks of age and AMPV subtypes A and B were detected via RT-PCR from both farms in this study. This is the first report of AMPV subtypes A and B by RT-PCR detection in Malaysia.